2021
DOI: 10.48550/arxiv.2103.04491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arbitrary controlled-phase gate on fluxonium qubits using differential ac-Stark shifts

Abstract: Large scale quantum computing motivates the invention of two-qubit gate schemes that not only maximize the gate fidelity but also draw minimal resources. In the case of superconducting qubits, the weak anharmonicity of transmons imposes profound constraints on the gate design, leading to increased complexity of devices and control protocols. Here we demonstrate a resource-efficient control over the interaction of strongly-anharmonic fluxonium qubits. Namely, applying an offresonant drive to non-computational t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…We have also shown that using the differential AC-Stark shift to realize a CZ entanglement gate gives an extra degree of freedom on the entanglement drive fre-quency and improves the yield of this architecture, thus improving the scaling possibility of this architecture. Fixed-frequency quantum processor with transmon is currently one of the most developed architectures for multi-qubit systems, however, other qubit designs like fluxonium [23] can also realize quantum processors and will have different frequency constraints that can potentially give an advantage over transmon in terms of yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that using the differential AC-Stark shift to realize a CZ entanglement gate gives an extra degree of freedom on the entanglement drive fre-quency and improves the yield of this architecture, thus improving the scaling possibility of this architecture. Fixed-frequency quantum processor with transmon is currently one of the most developed architectures for multi-qubit systems, however, other qubit designs like fluxonium [23] can also realize quantum processors and will have different frequency constraints that can potentially give an advantage over transmon in terms of yield.…”
Section: Discussionmentioning
confidence: 99%
“…Differential AC-Stark shift or SiZZle -A control-Z gate with simultaneous AC-Stark shift entangling gate has recently been proposed and demonstrated for both fluxonium [23] and transmon architectures [19,24] as an alternative to the CR gate. The constraints for this gate are similar to those for the CR case with the modification that the drive frequency can now vary between the frequency of the control and the target transmon.…”
Section: Frequency Collisionsmentioning
confidence: 99%
“…The Hamiltonian interaction term is written as ζσ z1 σ z2 , acting on the two qubits. Typically, in superconducting systems, it arises from the interaction of the |11 state with the non-computational state in the physical qubits, and can both be used as a resource for entangling gates [21][22][23][24] or viewed as cross-talk noise that needs to be suppressed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Physical Applicationsmentioning
confidence: 99%
“…One implementation is using a transmon and a capacitively shunt flux qubit (CSFQ) [25,26]. Other methods include using additional off-resonant drive [39][40][41] and different types of qubits have also been proposed [38].…”
Section: B Zz Coupling Suppression In the Quasi-dispersive Regimementioning
confidence: 99%
See 1 more Smart Citation